Water use Efficiency of Maize Crop Under Deficit Irrigation Scheduling using Gravity Drip System in Samaru, Nigeria (Global Journal of Science Frontier Research, 2017)
The use of gravity fed drip irrigation systems is fast gaining popularity in Northern Nigeria. The drip kit uses gravity instead of a pump to provide the head (energy) for its operation. The water source (a tank or bucket) is usually place some meters above the ground to provide the pressure head. In the study reported herein, a field experiments were carried out at the Institute for Agricultural Research (I.A.R) irrigation farm Samaru-Nigeria during 2012/2013 irrigation season to evaluate the effect of deficit irrigation scheduling, using the gravity drip kit, on yield and water use of a maize (SAMAZ 14 variety) crop. The field experiment consisted of eight treatments replicated three times. The treatments comprises of a control treatment which was given full irrigation (irrigated at 100 % water requirement) and a full deficit treatment which was irrigated at 50 % water requirement. The other treatments were irrigated at 50 and 75 % of water requirement at different growth stages of the maize crop. The irrigation interval was alternated between three and four days.
Keywords: emission uniformity; emitter; discharge; application efficiency; water use efficiency; crop yield